2010
DOI: 10.1029/2009gl042093
|View full text |Cite
|
Sign up to set email alerts
|

Mantle helium reveals Southern Ocean hydrothermal venting

Abstract: Hydrothermal venting along the global mid‐ocean ridge system plays a major role in cycling elements and energy between the Earth's interior and surface. We use the distribution of helium isotopes along an oceanic transect at 67°S to identify previously unobserved hydrothermal activity in the Pacific sector of the Southern Ocean. Combining the geochemical information provided by the helium isotope anomaly with independent hydrographic information from the Southern Ocean, we trace the source of the hydrothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Then in 2006, it was hypothesized that up to 50% of deep-ocean dissolved iron occurring in the Pacific Ocean may have come from hydrothermal sources throughout the past 10 million years (Chu et al, 2006). Since then, the "leaky vent" hypothesis has been supported by reports that chemical mechanisms protect iron from precipitation as minerals (Bennett et al, 2008;Toner et al, 2009) and that physical processes can prevent settling of minerals (Yücel et al, 2011 Ocean (Lupton, 1998;Winckler et al, 2010). Beyond the Southern Ocean, a more nuanced view of ocean circulation, where eddies play a larger role in overturning of water masses, is building.…”
Section: Assumptions Asidementioning
confidence: 73%
“…Then in 2006, it was hypothesized that up to 50% of deep-ocean dissolved iron occurring in the Pacific Ocean may have come from hydrothermal sources throughout the past 10 million years (Chu et al, 2006). Since then, the "leaky vent" hypothesis has been supported by reports that chemical mechanisms protect iron from precipitation as minerals (Bennett et al, 2008;Toner et al, 2009) and that physical processes can prevent settling of minerals (Yücel et al, 2011 Ocean (Lupton, 1998;Winckler et al, 2010). Beyond the Southern Ocean, a more nuanced view of ocean circulation, where eddies play a larger role in overturning of water masses, is building.…”
Section: Assumptions Asidementioning
confidence: 73%
“…However, the Antarctic region has not been widely explored for hydrothermal activity, mainly because of its remoteness and the hostile environment associated with high latitudes. Nevertheless, evidence for hydrothermal activity in the Southern Ocean has been established for more than a decade, primarily based on observations of chemical anomalies in the water column [3], [4], [5]. Because of the relative isolation of Antarctic hydrothermal fields from other hydrothermal systems and the mid-ocean ridge system, their occurrence has important implications for the distribution and evolution of vent-associated fauna.…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, Johnson and Talley (1997) compared stratification measures and temperature-salinity anomalies with d 3 He to trace various pathways of the hydrothermal plumes that had originated along the East Pacific Rise. Here, we expand upon the analysis of Winckler et al (2010) by showing that the d 3 He signature they observed coincides with a distinct potential vorticity signal in the deep South Pacific sector of the Southern Ocean. Winckler et al (2010) identified the Pacific-Antarctic Ridge as a major hydrothermal plume source that can be traced via a d 3 He plume along the 28.2 kg m 23 neutral density surface (s 2 ' 1037.12 kg m 23 ) south of the ridge along 1508W and across the 678S cruise transect.…”
Section: Introductionmentioning
confidence: 68%
“…Stommel (1982) concluded that heat in the buoyant plumes from hydrothermal vents is effectively diffused unless ''competing mechanisms are not overpowering.'' Hydrothermal vents are apparently common along midocean ridges, but with a highly intermittent distribution; they have recently been identified on parts of the 2600-km-long Pacific-Antarctic Ridge, southwest of the East Pacific Rise (Winckler et al 2010). Hydrothermal vents are apparently common along midocean ridges, but with a highly intermittent distribution; they have recently been identified on parts of the 2600-km-long Pacific-Antarctic Ridge, southwest of the East Pacific Rise (Winckler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation